PERANCANGAN MEDIA PEMBELAJARAN INTERAKTIF SISTEM TATA SURYA BERBASIS FLASH - Khairiah Khairiah; Dewi Maharani; Endra Saputra (LPPM STMIK Royal Kisaran, 2023)
Abstract: Learning media is one of the learning tools used by someone using a tool made to facilitate the delivery of material when teaching at school. In general the system learning that is implemented in schools is still done manually, at UPT schools. SD Negeri 04 Padang Genting learning system that is still running today Still manually, learning media has not been implemented manually by computerization, especially science subjects (natural sciences) on the material solar system. learning methods that are still manual make teachers having difficulty teaching the solar system material to students, students also find it difficult to understand the material taught by the teacher so that makes students feel bored. Then the need for interactive learning media solar system to improve the quality of teacher teaching and learning. Media learning is made with Adobe Flash CS6. The conclusion is to make it easier for teachers to provide explanations and learning of the grammar system solar to students/female students, because there is quiz as evaluation material, drawings move and sound on the solar system interactive learning media have made. Keywords: solar system; interactive learning media Abstrak: Media pembelajaran merupakan salah satu sarana pembelajaran yang digunakan oleh seseorang dengan menggunakan alat yang dibuat untuk memudahkan dalam penyampaian materi ketika mengajar di sekolah. Pada umumnya sistem pembelajaran yang diterapkan di sekolah masih secara manual, pada sekolah UPT. SD Negeri 04 Padang Genting sistem pembelajaran yang masih berjalan saat ini masih secara manual, belum diterapkannya media pembelajaran secara komputerisasi terutama mata pelajaran IPA (Ilmu pengetahuan alam) pada materi sistem tata surya. cara pembelajaran yang masih manual membuat guru mengalami kesulitan untuk mengajarkan materi sistem tata surya kepada siswa/siswinya, siswa juga sulit memahami materi yang diajarkan guru sehingga membuat siswa merasa jenuh. Maka dibutuhkannya media pembelajaran interaktif sistem tata surya untuk meningkatkan kualitas belajar mengajar guru. Media pembelajaran dibuat dengan Adobe Flash CS6. Tujuan dari penelitian ini adalah mempermudah Guru UPT. SD Negeri 04 Padang Genting dalam memberi pelajaran untuk siswanya. Hasil dari penelitian ini untuk mempermudah guru dalam memberikan penjelasan dan pembelajaran sistem tata surya kepada siswa/siswi, karena terdapat kuis sebagai bahan evaluasi, gambar bergerak dan suara pada media pembelajaran interaktif sistem tata surya yang telah dibuat. Kata kunci: sistem tata surya; media pembelajaran interaktif